FDI and firm productivity: A comprehensive review of macroeconomic and microeconomic models - Eleonora Santos (Economies, 2023)
This paper reviews the literature on foreign direct investment (FDI), productivity, and technology upgrading, with a focus on macroeconomic and microeconomic models. It compares the performance of various models used to study FDI and its effects on firms' productivity, via skill and technology upgrading, offshoring, institutional quality, and other related factors. This review highlights the differences and similarities between macroeconomic and microeconomic models, their empirical strategies, and their ability to provide a comprehensive understanding of the mechanisms through which FDI affects productivity and other variables. The empirical literature on the impact of FDI on the productivity of local firms is derived from association studies, which use a neoclassic production function and an augmented Solow-type equation. These models have been shown to be inadequate in capturing the dynamic and complex nature of FDI and the associated externalities, particularly vertical externalities. This paper identifies three criticisms of the literature on pecuniary externalities, including a lack of models that focus specifically on the mechanism of forward linkages, inadequate measures to assess linkage effects, and the failure to include crucial determinant factors in empirical models. Overall, this paper calls for more comprehensive and nuanced models that incorporate the dynamic and complex nature of FDI and its externalities.
Keywords: 330; foreign direct investment; productivity; technology upgrading; externalities